Pengaruh Self-Confidence Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Haila Rianti; Anggun Sefta Amelia; Wardiatul Ahnani; Dewintan Anyelir; Netriwati Netriwati (Griya Journal of Mathematics Education and Application, 2026)
This study aims to investigate and identify the relationship between students’ self-confidence and their ability to solve mathematical problems. Empirical findings indicate that students still demonstrate relatively low ability in solving mathematical problems. Therefore, the background of this study requires further analysis of the factors that contribute to this issue. To examine how the variables are related, this study employs a quantitative approach with a correlational research design. The data collection techniques include questionnaires to measure students’ self-confidence and tests to assess their ability to solve mathematical problems. Data were collected through questionnaires to measure the level of self-confidence and tests based on specific indicators to evaluate problem-solving abilities in mathematics. To test the research hypothesis, the data were analyzed using normality tests and simple linear regression analysis. The findings reveal that self-confidence does not have a significant effect on students’ ability to solve mathematical problems. However, students with higher levels of self-confidence tend to have better conceptual understanding and problem-solving abilities. These results indicate that, in addition to self-confidence, there are other factors that also influence mathematical problem-solving ability, and some of these factors may play a more dominant role.